IMPROVING CRITICAL THINKING ABILITY THROUGH MAKE A MATCH MODEL ASSISTED BY PUZZLE MEDIA AT ELEMENTARY SCHOOLS - Ainun Fisabilillah Dina Wulan N; Ika Ari Pratiwi; Erik Aditia Ismaya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research aimed to improve students’ critical thinking skills through make a match model assisted by puzzle media for elementary school students in the even semester of the academic year 2019/ 2020. This research was a Classroom Action Research (CAR) conducted in 2 cycles by using make a match as a learning method and puzzle as a learning medium. The subjects of this study were 26 students at grade V SD 3 Adiwarno, which consisted of 14 male students and 12 female students. The research data were collected by using the learning outcome test in the form of description question and non-test technique (interviews, observation, and documntation). The data from the test were analyzed descriptively and quantitatively. At the pre-cycle stage consisting of PPKn and Social Science, the result of critical thinking test obtained an average of classical learning completeness of 1846 with a percentage of 44% (fairly good category). Then, the result of classical learning completeness obtained in cycle Iwas 2025 with a percentage of 73% in good category. Moreover, the result of classical learning completeness in cycle II was 2125 with a percentage of 85% in very good category. Thus, it could be concluded that make a match model assisted by puzzlemedia improved stuednts’ critical thinking skills